The labour market effects of VAT harmonisation in a multicountry AGE model - Alan Duncan; John Hutton; Fouad Laroui; Anna Ruocco (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
This paper considers the sensitivity of policy simulation to the specification of the labour market in an Applied General Equilibrium (AGE) model of the European Union. We consider a variety of adjustments to the labour market, including the introduction of labour supply heterogeneity and involuntary unemployment, and examine how those adjustments influenae the simulated impact of a move to European VAT harmonisation. Empirical results indicate that the precise mechanism by which unemployment is factored into the AGE model has important consequences for the price, quantity and welfare effects following the policy reform.
Keywords: 330